Tertiary students' perceptions of mobile technology enhanced learning environments and associations with outcomes in New Zealand - Snell-Siddle, Catherine (Curtin University, 2012)
This thesis describes research that investigated associations between students’ perceptions of mobile technology enhanced learning environments and tertiary students’ outcomes. A review of the literature examined a range of topics pertaining to the study which encompassed the use of technology in higher education, theoretical approaches to learning, modes of learning, the emerging body of research in mobile learning, learning environment instruments, and the associations between classroom environment and student cognitive and attitudinal outcomes. This study used a modified form of the Web-based Learning Environment Instrument (WEBLEI), renamed the Mobile Enhanced Learning Environment Instrument (MOBLEI), to gather quantitative data about the associations between students’ perceptions of mobile technology enhanced learning environments and student outcomes in a tertiary environment that uses different delivery modes.Qualitative data on students’ perceptions were collected by discussion questions added to the MOBLEI questionnaire and through follow-up focus groups. The study has synthesised results from both quantitative and qualitative sources and has provided an understanding as to how students perceive their mobile enhanced learning environments. The research has made a valuable contribution to the field of learning environment research by developing a new learning environment instrument that can be used with confidence in tertiary institutions in New Zealand to evaluate the increasing uptake of mobile technologies that are being used in an effort to enhance learning. It has also been able to provide insight into the associations that exist between students’ perceptions of their mobile enhanced learning environments and their attitudinal and cognitive outcomes.